Islamic Activity Management Of Housewives In A Multi-Ethnic Village - Syafnan, Syafnan; Lisnasari, Srie Faizah; Lubis, Fitriani Surayya (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to reveal the morals of housewives in multi-ethnic villages, and border areas of the Province, both in the event of grief, joy, and village government activities. The research methodology is a qualitative phenomenological model, with the key data source being 16 housewives aged 30 to 47 years, the instrument used is a structured interview guide and processing data starting from the collection, validation, analysis, triangulation, and making conclusions. Research results:Â  The morals of Batusondat village housewives outside the home towards bereavement activities, Islamic behavior of Batusondat village housewives outside the home in responding to joy is: visiting with polite clothes and not newly bought ones. While in Sukamaju village are: visiting with polite clothes but with newly bought clothes, Batu Sondat village housewives apply the Islamic leadership model in fostering their children's morals by prioritizing giving examples of behaving in an Islamic manner. While in Sukamaju village: prioritizing a simple lifestyle, The contribution shown by housewives of Batusondat village in participating in the youth moral development program in the village PKK/Jorong is by giving the energy to do activities in activities and also giving money to participate in activities according to sincerity.